C−C Coupling of Benzyl Fluorides Catalyzed by an Electrophilic Phosphonium Cation. (30th May 2016) - Zhu, Jiangtao; Pérez, Manuel; Stephan, Douglas W.
Abstract: The activation and cleavage of benzyl fluorides by the electrophilic organofluorophosphonium catalyst, [(C6 F5 )3 PF][B(C6 F5 )4 ], is reported and used for the preparation of 1, 1‐diarylalkanes (37 examples) and substituted aryl homoallylic alkenes (14 examples). This procedure involves mild conditions, avoids harmful waste, and is compatible with a range of substituted arenes and allylic silanes.